2007
DOI: 10.1200/jco.2006.08.9672
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Imexon in Patients With Advanced Malignancy

Abstract: The phase II recommended dose of imexon is 875 mg/m2/d for 5 days every other week. A decrease in plasma thiols did correlate with imexon exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 22 publications
2
44
0
2
Order By: Relevance
“…Mean imexon peak plasma levels in the current trial were 62.0 lg/mL for a 30-minute infusion of 1000 mg/m 2 , compared with 97.3 lg/mL in the prior phase 1 trial of singleagent imexon. 20 Clearance and volume of distribution values were also similar in the 2 trials. The mean (standard deviation) imexon AUC of 8947 (AE3639) lg/mL/min in the prior trial, which included 1 high AUC outlier, 20 is comparable to the mean (standard deviation) imexon AUC of 5436 (AE1578 lg/mL/min) seen in the 8 patients studied in the current trial.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Mean imexon peak plasma levels in the current trial were 62.0 lg/mL for a 30-minute infusion of 1000 mg/m 2 , compared with 97.3 lg/mL in the prior phase 1 trial of singleagent imexon. 20 Clearance and volume of distribution values were also similar in the 2 trials. The mean (standard deviation) imexon AUC of 8947 (AE3639) lg/mL/min in the prior trial, which included 1 high AUC outlier, 20 is comparable to the mean (standard deviation) imexon AUC of 5436 (AE1578 lg/mL/min) seen in the 8 patients studied in the current trial.…”
Section: Discussionmentioning
confidence: 51%
“…Also, nonsignificant differences were observed for the AUC 0-t (which ranged from 55.3 to 82.1 hours  lg/mL), the t 1/2 , which averaged about 1 hour, drug clearance, which ranged from 15.0 to 22.8 L/h/m 2 , and the V ss , which ranged from 15.0 to 22.8 L/m 2 . As in the prior phase 1 pharmacokinetic study, 20 the V ss of imexon was greater than extracellular water, but less than total body water, which suggests limited penetration into tissues. There was no difference between pharmacokinetic parameters in the 4 men and 2 women for the 30-minute imexon infusion (data not shown).…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 84%
See 2 more Smart Citations
“…13,14 Phase 1 trials demonstrated imexon to be well tolerated, associated with symptoms of reversible fatigue and gastrointestinal side effects with a relative lack of severe myelosuppressive toxicities. 15,16 Although few lymphoma patients were enrolled in the early phase 1 studies, a partial response (PR) was noted in a patient with follicular lymphoma (FL).…”
Section: Introductionmentioning
confidence: 99%